Operations, Logistics and Supply Chain Management - Zijm, Henk; Klumpp, Matthias; Regattieri, Alberto; Heragu, Sunderesh (Lecture Notes in Logistics, 2018)
This book provides an overview of important trends and developments in logistics and supply chain research, making them available to practitioners, while also serving as a point of reference for academicians.